Roles of MASP-1 and MASP-3 in the development of retinal degeneration in a murine model of dry age-related macular degeneration - Omori, Tomoko; Machida, Takeshi; Ishida, Yumi; Sekiryu, Tetsuju; Sekine, Hideharu (Frontiers in Immunology, 2025)
Complement is activated through the three different pathways, which are the classical (CP), lectin (LP), and alternative pathways (AP). Complement activation functions to eliminate invading pathogens, whereas dysregulation of complement activation can induce inflammatory disorders such as age-related macular degeneration (AMD). In retinal degeneration induced by sodium iodate (NaIO3), a murine model of dry AMD (also called atrophic AMD), it has been suggested that the AP and CP are involved in the disease development. On the other hand, the role of the LP in the development of AMD remains unclear. In the current study, we generated murine dry AMD model with NaIO3 using mice deficient for mannose-binding lectin-associated serine protease (MASP)-1 and/or MASP-3, which are required for the LP and AP activation, respectively. Wild-type (WT) C57BL/6J mice showed retinal degeneration, including depigmentation and disruption of the retinal pigment epithelium (RPE), atrophy of the photoreceptor layer (PL), and thinning of the outer nuclear layer (ONL) after NaIO3 injection. In contrast, those pathological changes after NaIO3 injection were significantly attenuated in MASP-1-deficient (MASP-1-/-), MASP-3-deficient (MASP-3-/-), and MASP-1/3-double deficient (MASP-1/3-/-) mice. These results indicate that both MASP-1 and MASP-3 play a role in photoreceptor degeneration in the NaIO3-induced murine dry AMD model. In addition, photoreceptor cell death and retinal C3 activation were observed in NaIO3-injected WT mice, whereas those pathological changes were significantly attenuated in NaIO3-injected MASP-3-/- and MASP-1/3-/- mice. On the other hand, those pathological changes in NaIO3-injected MASP-1-/- mice were comparable to those in NaIO3-injected WT mice. Taken together, our results indicate that MASP-3 plays a pivotal role in C3 activation in the retina most likely via activation of the AP leading to the development of retinal degeneration in the NaIO3-induced murine dry AMD model. Our results also indicate that MASP-1 plays a role in the development of NaIO3-induced retinal degeneration in this murine model, although it remains unclear whether its role in the retinal degeneration is through the LP activation.